Mobile Commerce 2018
DOI: 10.4018/978-1-5225-2599-8.ch063
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Factors Affecting Mobile Shopping in Taiwan

Abstract: Mobile commerce has already become one of the trends in future developments. Therefore, mobile shopping in application of mobile commerce will become one of the services with a vast development potential. A technology acceptance model (TAM) with trust is utilized to explore influence of perceived ease of use and perceived usefulness in mobile shopping on customers' attitudes and behavioral intention to use, mobility, convenience and information richness, characterized by mobile commerce. An online survey was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
0
0
2
Order By: Relevance
“…Past inquiries have revealed that elements fostering the affirmative embrace of mobile shopping involve the genuineness of information [5], the aesthetic aspects of retail design [11], seamless integration and coherence in multi-channel systems [12], the realization of expectations [13], the impact of brand influence [14], and the proficiency level in system, information, and service [15].These studies substantiate that the embrace of mobile shopping by consumers is favorably associated with vendor satisfaction [2], trustworthiness, and the capacity to challenge the inertia toward vendor change [14]. [16] in their study on voice-based artificial intelligence technologies, suggest that trust in technology is an important determinant that leads to user acceptance.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Past inquiries have revealed that elements fostering the affirmative embrace of mobile shopping involve the genuineness of information [5], the aesthetic aspects of retail design [11], seamless integration and coherence in multi-channel systems [12], the realization of expectations [13], the impact of brand influence [14], and the proficiency level in system, information, and service [15].These studies substantiate that the embrace of mobile shopping by consumers is favorably associated with vendor satisfaction [2], trustworthiness, and the capacity to challenge the inertia toward vendor change [14]. [16] in their study on voice-based artificial intelligence technologies, suggest that trust in technology is an important determinant that leads to user acceptance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The intention to purchase by consumers is the indicator that suggests a consumer will exhibit a particular behavior. Customers intent to buy from a mobile shopping app depends on their level of trust in the mobile vendor, or the level of care the vendor has for their customers welfare [2], past purchasing history [3], privacy and security when making transactions [4], the calibre and accuracy of the information supplied on these applications [5]. Establishing trust has been recognized as a pivotal factor in fostering online transactions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Además, las empresas deben tratar de mejorar la eficiencia del proceso de compra a través del comercio móvil, incorporando más información relevante sobre los productos -por ejemplo, comentarios de otros consumidores que hayan adquirido previamente un producto y fotografías reales de este (Li, Huang, Tan y Wei, 2013)-que proporcionen a los individuos información de utilidad para la compra. Igualmente, deben utilizar herramientas que permitan la comparación de precios con los de la competencia, o incorporar la opción de "compra en un click" (Chen y Lan, 2018), que recuerda los datos del consumidor y permite realizar la compra ahorrando tiempo y esfuerzo. Analizando el uso de la opción de compra en un click, las empresas podrían identificar a los consumidores con altas necesidades de recursos materiales y tratar de potenciar este rasgo mediante el uso de pop-ups con productos personalizados o a través de sugerencias u ofertas especiales de productos que se adapten a sus gustos.…”
Section: Implicaciones Empresarialesunclassified
“…La mayoría de los estudios realizados sobre el comercio móvil están basados en el modelo TAM (por ejemplo, Bruner y Kumar, 2005;Chen y Lan, 2018;Faqih y Jaradat, 2015;Jiménez et al, 2019;Luarn y Lin, 2005;Natarajan et al, 2017Natarajan et al, , 2018Vahdat, Alizadeh, Quach y Hamelin, 2020;Wu y Wang, 2005), al que le han ido añadiendo diversas variables con el fin de extender y completar el modelo. Este modelo, propuesto por Davis (1989), se centra fundamentalmente en las percepciones internas de los consumidores, y establece que la decisión de utilizar una tecnología viene determinada por la facilidad de uso y por la utilidad percibida de la tecnología en cuestión.…”
Section: Introductionunclassified